Treatment of severe bone defects during revision total knee arthroplasty with structural allografts and porous metal cones-a systematic review - Beckmann, Nicholas A.; Jäger, Sebastian; Reiner, Tobias; Bitsch, Rudi G. (The journal of arthroplasty, 2015)
Aseptic loosening and focal osteolysis are the most common reasons for knee arthroplasty failure. The best treatment remains unclear. We reviewed the literature on the treatment of revision knee arthroplasty using bony structural allografts (476 cases) and porous metal cones (223 cases) to determine if a difference in the revision failure rates was discernable. The failure rates were compared using a logistic regression model with adjustment for discrepancies in FU time and number of grafts used (femoral, tibial, or both). In this analysis, the porous implant shows a significantly decreased loosening rate in AORI 2 and 3 defects. The overall failure rate was also substantially lower in the porous metal group than the structural allograft group; little difference in the infection rates was noted.
Published online: 11 September 2014
Gesehen am 26.06.2017